Adobe After Effects CC 2017 release - Gyncild, Brie; Fridsma, Lisa (Classroom in a book, 2017)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe After Effects CC (2017 release) choose Adobe After Effects CC Classroom in a Book (2017 release) from Adobe Press. The 14 project-based lessons in this book show users step-by-step the key techniques for working in After Effects. Learn how to create, manipulate, and optimize motion graphics for film, video, DVD, the web, and mobile devices. Gain hands-on experience animating text and images, customizing a wide range of effects, tracking and syncing content, rotoscoping, and correcting color. Learn to create 3D content with both After Effects and Maxon Cinema 4D Lite (included with the software).